Correlation between adversity quotient and job performance of LGU employees of Tayabas City input to effective public personnel management - Ablaña, Michael Vincent V. (Tilamsik, 2016)
This study was conducted to determine the relationship of Adveristy Quotient and job performance of the City government employees in Tayabas. Specifically, the study sought to determine the following: the demographic profile of the employees, the Adversity Quotient; the relationship between demographic profile and AQ; and the relationship between AQ and job performance. The researchers utilized a descriptive-correlation design which made use of two sets of questionnaire: the first is that which determined the demographic profile of respondents; and the second is the online AQ profile from PEAK Learning. Data on job performance was based on the Strategic Performance Management System (SPMS). Findings showed that adversity quotient does not dictate how an employee performs at work and does not impact job performance.